Influencing online grocery innovation: Anti-choice as a trigger for activity fragmentation and multi-tasking. - de Kervenoael, Ronan; Elms, Jonathan; Hallsworth, Alan (Futures)
This paper reveals how activity fragmentation and multi-tasking become tools of consumer anti-choice in the online grocery sector: facilitated by new technology practices that positively encourage anti-choice. This is demonstrated through five long-term ethnographic case studies of households in the Portsmouth area of England. All the respondents made some form of conscious effort to minimize the amount of time they spent in ‘big box’ grocery stores. They spend more time at home in planning, searching, socializing online, cumulating and fulfilling internet orders than if they had visited a store: something that all could easily do. The findings suggest the need for constant innovation by internet grocers if they are to remain in tune with dynamic consumer lifestyles and advances in technology. Examples of upcoming technologies requiring retailers to re-think their internet strategies are discussed in view of the possibilities offered by activity fragmentation and multi-tasking.